Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan Madrasah Tsanawiyah - Khairil Anwar (Lembaga Yasin AlSys, 2026)
Madrasah principals’ leadership is a strategic factor in improving educational quality, particularly in Madrasah Tsanawiyah, which carry integrated academic, character, and Islamic responsibilities. However, studies that systematically map madrasah principals’ leadership strategies, supporting and inhibiting factors, and their impact on educational quality still need to be strengthened. This study aims to analyze madrasah principals’ leadership strategies in improving educational quality in Madrasah Tsanawiyah. This study used a qualitative approach with a library research design. Data were obtained through documentation of scientific books, journal articles, and relevant documents discussing educational leadership, madrasah management, academic supervision, and educational quality. The data were analyzed using content analysis through the stages of data reduction, theme categorization, data display, and conclusion drawing. The results showed that madrasah principals play roles as leaders, managers, supervisors, motivators, innovators, and drivers of a quality culture. The dominant strategies used include transformational, visionary, and participatory leadership, continuous academic supervision, teacher professional development, and strengthening cooperation with stakeholders. The success of these strategies is supported by human resource competence, the availability of facilities and infrastructure, a collaborative culture, and community support, but is hindered by limited resources, resistance to change, and suboptimal program evaluation. The conclusion of this study affirms that adaptive, participatory, and quality-oriented madrasah principal leadership contributes to improving the quality of learning, teacher professionalism, organizational culture, and public trust. These findings imply the importance of strengthening madrasah principals’ leadership capacity in building educational governance that is collaborative, sustainable, and responsive to the quality needs of madrasah education.